Synthesis of 2-Aryl and 2-Vinylpyrrolidines via Copper-catalyzed Coupling of Styrenes and Dienes with Potassium β-Aminoethyltrifluoroborates - Um, Chanchamnan (Org Lett, 2016)
2-Arylpyrrolidines occur frequently in bioactive compounds and thus methods to access them from readily available reagents are valuable. We report a copper-catalyzed intermolecular carboamination of vinylarenes with potassium N-carbamoyl-β-aminoethyltrifluoroborates. The reaction occurs with terminal, 1,2-disubstituted and 1,1-disubstituted vinylarenes bearing a number of functional groups. 1,3-Dienes are also good substrates and their reactions give 2-vinylpyrrolidines. Radical clock mechanistic experiments are consistent with the presence of carbon radical intermediates and do not support participation of carbocations.